Patterns of antibiotic use in hospital-acquired infections. (August 2021) - Sevin, T.; Daniau, C.; Alfandari, S.; Piednoir, E.; Dumartin, C.; Blanchard, H.; Simon, L.; Berger-Carbonne, A.; Le Vu, S.
Summary: Background: Monitoring the use of antimicrobials in hospitalized patients is critical owing to the risk of resistance selection. This study aimed to describe the patterns of antimicrobial prescription for the most frequent healthcare-associated infections (HAIs) in France, relating drugs and microbiological data. Methods: We used data from the 2017 point-prevalence survey of HAI and antimicrobial use in France, a large nationally representative sample survey of inpatients. We sought unambiguous correspondence between individual indications of antibiotic regimen and HAI sites to determine which molecules were directed towards which pathogen, considering its resistance profile. Results: Among 75, 698 adult patients from 401 hospitals, 5.1% had an active HAI and 4.3% were being treated for an HAI. The two most frequent antibiotic indications were lower respiratory tract (LRTI, 27.7%) and urinary tract infections (UTI, 18.4%). For LRTI, the most prescribed antibiotic was amoxicillin-clavulanic acid (27.6%) and most frequently isolated pathogens (each accounting for around 17% of isolates) were Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli . Meticillin-resistant S. aureus LRTI was more likely to be treated with linezolid. For UTI, ofloxacin, ceftriaxone, amoxicillin/co-amoxiclav were most-prescribed (∼13% each) and E. coli predominantly isolated (52.0%). Extended-spectrum beta-lactamase-producing E. coli UTI were more likely treated by fosfomycin, pivmecillinam or ertapenem. Conclusions: This study provides a baseline of antimicrobial use in relation to microbiological information in patients with the most common HAIs. These results can serve to direct future efforts in antimicrobial stewardship. Our work could be extended to a broader population, notably in Europe where similar surveys have been conducted.